Evaluation of bile acid and deranged liver function test in obstetrics cholestasis in pregnancy in fetal and perinatal outcome - Mani, Poonam; Sachdeva, Rishika; Chaudhary, Neeta; Chhabra, Nikshima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy-related intrahepatic cholestasis is most prevalent hepatic disorder intense pruritus that affects the entire body including palm and sole. It is typically detected during second or third trimester. Pruritus frequently exacerbates at night, marked on the palms and soles of the feet and hands. Aim of this study was to evaluate bile acid and deranged liver function test in obstetrics cholestasis in pregnancy and to determine maternal fetal and outcomes. Methods: This prospective case series study was conducted in the Department of Obstetrics and Gynaecology, Muzaffarnagar Medical College. The present study was conducted in 50 women, who were selected from outpatient department of antenatal care from tertiary care, taken written permission before study. The medical records of all women with obstetrics cholestasis who delivered between December 2021and August 2022. Results: Subjects with IHCP has mean age of 30.11±5.03 year, found SGOT 40% in 100-200 and SGPT 44 % I (0-100) range and total bilirubin levels is 33 % in IHCP patients. In study found that LSCS due to 24% in fetal distress, 36% in MSL, 16% in IUGR, 14% preterm. Participants have 22% birth weight <2.5kg and 39 (78%) are under >2.5kg babies in IHCP patients and 24 % were underwent fetal distress and 24 % preterm delivery and 6 % got IUD . and no stillborn and 12% meconium. Conclusions: It causes maternal pruritus with impaired LFT and raised serum bile acids. Maternal morbidity is increased in terms of increased LSCS rates and discomfort due to pruritus.